Colorimetric Determination of p-Phenylenediamine Using Silver Nanoparticles Modified with Poly(ethylene glycol) Methyl Ether Thiol - Lee, Sujin; Nam, Yun-Sik; Nah, In Wook; Lee, Yeonhee; Lee, Kang-Bong (AMER SCIENTIFIC PUBLISHERS, 2017)
A sensitive and selective colorimetric method for the determination of p-phenylenediamine (PPD) in aqueous samples was developed using silver nanoparticles functionalized with poly(ethylene glycol) methyl ether thiol (PEG.MET). PPD acts as a bridge between two PEG.MET-AgNPs, in which the two NH2 groups of PPD are hydrogen-bonded to the oxygen atoms of PEG.MET-AgNPs, shortening the interparticle distance and inducing the aggregation of the PEG.MET-AgNPs. The binding site and sensing mechanism of PPD by PEG.MET-AgNPs were characterized by Fourier transform infrared spectroscopy, ultraviolet-visible (UV-vis) spectroscopy, and transmission electron microscopy. This aggregation resulted in a dramatic color change from yellow to reddish brown. Using this methodology, the concentration of PPD in environmental samples can be quantitatively detected by the naked eye or by using UV-vis spectrometry. Also, we found that the sensitivity of the detection noticeably improved at a pH of around 6, wherein a more obvious color change was observed. The absorbance (A(310)) of the modified AgNP solution exhibited a linear correlation with the PPD concentrations of 0.002-1.5 mM, and the limit of detection was 0.53 mu M. This cost-effective sensing system allows for the rapid and facile determination of PPD in aqueous samples.
Keywords: LIQUID-CHROMATOGRAPHY; DNA-DAMAGE; HAIR-DYES; GOLD; PEG; SAMPLES; METABOLITES; PRODUCTS; SENSORS; PROBE